Career experiences of African American police executives : black in blue revisited - Thompson, R. Alan (Criminal justice (LFB Scholarly Publishing LLC), 2003)
Thompson studies the career experiences of over 100 black police executives, many of whom command some of the nation's largest and most progressive law enforcement agencies. Considering their relationships with white colleagues as well as black and white citizens, he asks them what it was like to advance through the ranks of a historically white-dominated profession. Thompson examines common assumptions regarding the careers of these professionals, all of whom confronted, yet overcame, considerable opposition and discrimination. The results of this unprecedented exploration provide readers as well as aspiring black police executives with unique insight into the events that have shaped the philosophies of these increasingly influential social policy leaders.